Robust longitudinal motion control of underground mining electric vehicles based on fuzzy parameter tuning sliding mode controller. (March 2022) - Ye, Wenjie; Shen, Weixiang; Qian, Zhe; Zheng, Jinchuan
Abstract: The desire to reduce costs and increase productivity is driving mining industries to deploy underground mining electric vehicles (UMEVs). Due to the complex, working environments in underground mines, safer and more stable control strategies of UMEVs are required than the conventional control approaches used for electric vehicles (EVs). In this paper, first a UMEV model with bounded system uncertainties is derived. Next, a fuzzy parameter tuning (FPT) technique is used to adjust parameters in the sliding mode controller (SMC) against unexpected external disturbances and unbounded system uncertainties, which significantly improves system stability and robustness. Simulation and experimental results demonstrate that the proposed fuzzy parameter tuning sliding mode controller (FPTSMC) achieves better performance than SMCs with parametric uncertainties.